Response Analysis of Training Participants in Making E-Module Using Flip PDF Corporate for Teachers at SD IT Insan Mulia, Bengkulu City - Dedy Hamdani; Eko Risdianto (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2022)
This study aims to discuss the success rate of training activities based on the results of the response analysis of training participants in making e-modules using flip pdf corporate for teachers at SD It Insan Mulia, Bengkulu City. This research was conducted in July-August 2022. The target audience for this service activity is the education community. namely SD IT Insan Mulia, Bengkulu City. The target of this service is the teachers at SD IT Insan Mulia, Bengkulu City who will benefit from this training activity. In the plan for this service activity, observations have been made and the adequacy of facilities and infrastructure for training activities and there is support from the school which states that it welcomes this service activity to be carried out at SD IT Insan Mulia, Bengkulu City. The activity began with observations and interviews with a number of teachers and principals of SD IT Insan Mulia, Bengkulu City about the needs needed to assist teachers in making electronic teaching materials, especially those that can be used in the midst of the current pandemic. To measure the success of this activity, the team conducted evaluations and surveys in the form of questionnaires distributed to teachers. These results were then analyzed descriptively. The training activity for making e-modules using a corporate flip pdf for teachers at SD IT Insan Mulia, Bengkulu City was successfully carried out, this was evidenced by the positive response from the training participants to the training activities shown through the answers selected on the response questionnaire sheet.